1957
DOI: 10.1037/h0047849
|View full text |Cite
|
Sign up to set email alerts
|

Contingent partial reinforcement and the anticipation of correct alternatives.

Abstract: Estes and Straughan (6) developed an equation for the two-choice noncontingent reinforcement situation.Here S has two alternative responses either one of which may be followed by one of two environmental events. The occurrence of the events is controlled entirely by E and is independent of S's choices. A typical situation is one where there are two levers (alternative responses) with a light over each one (environmental events); S is to predict which light is going to flash next by pressing one of the levers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1958
1958
1975
1975

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In some two-choice probabilitylearning studies, human Ss given contingent reinforcement matched their choice percentages to the reinforcement percentages when the probabilities of positive reinforcement summed to one (Goodnow & Postman, 1955;Neimark, 1956;Sidowski & Gregovich, 1963). In others, 6s tended to overshoot the probabilitymatching percentages (Brand, Sakoda, & Woods, 1957;Bush & Mosteller, 1955, pp. 294-296;Edwards, 1956;Morin, 1955;Wyckoff & Sidowski, 1955).…”
mentioning
confidence: 99%
“…In some two-choice probabilitylearning studies, human Ss given contingent reinforcement matched their choice percentages to the reinforcement percentages when the probabilities of positive reinforcement summed to one (Goodnow & Postman, 1955;Neimark, 1956;Sidowski & Gregovich, 1963). In others, 6s tended to overshoot the probabilitymatching percentages (Brand, Sakoda, & Woods, 1957;Bush & Mosteller, 1955, pp. 294-296;Edwards, 1956;Morin, 1955;Wyckoff & Sidowski, 1955).…”
mentioning
confidence: 99%
“…At the same time, it has been found that under certain conditions Ss tend to maximize their frequency of choosing the more frequently reinforced stimulus. Among these are the presentation of a gambling task or a game of skill rather than a problem-solving task (7,9), an increased number of training trials (3,6), the presence of a distracting stimulus (18,19), and the lack of information concerning the appropriateness of some responses (2,3,14).…”
mentioning
confidence: 99%
“…Apparatus.-The two-choice contingent reinforcement apparatus used has been fully described elsewhere (Brand et al, 1957). Briefly, it consists of two levers (microswitches) at table height in front of 5 and a vertical panel containing red and white reinforcing lights and a green signal light.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the contingent equation for a two-choice situation takes the following form (Brand, Sakoda, & Woods, 1957):…”
mentioning
confidence: 99%